Interpretation of damage caused by a vapor cloud explosion. Issue 2 (13th November 2019) - Johnson, D. Michael; Pekalski, Andrzej; Tam, Vincent H. Y.; Burgan, Bassam A.; Hoorelbeke, Pol; Savvides, Chris; Allason, Daniel
Abstract: The understanding of vapor cloud explosions (VCEs) has changed significantly over recent years. Whereas it had been previously considered that VCE incidents had involved only deflagrations restricted to well‐defined congested process regions, it is now widely accepted that deflagration to detonation transition (DDT) has been involved in major VCE incidents. Once DDT occurs, high pressures will be generated throughout any remaining unburned cloud, not just the congested process region. The stimulus for this change in understanding was the research conducted following the Buncefield incident in the UK in 2005; however, the conclusions have been found relevant to other VCE incidents. In the process of both conducting the research and reviewing VCE incidents, a significant amount of data have been obtained on the effects of VCEs on items within and around the flammable cloud. These data will be of significant value in the interpretation of the forensic evidence produced in any future VCE. This article reviews the data available from the research and shows how it can be used in the investigation of any future VCE incidents.